INISIASI MENYUSU DINI (IMD) SEBAGAI FAKTOR PROTEKSI KEJADIAN STUNTING ANAK USIA 6 - 24 BULAN DI KOTA YOGYAKARTA - , Yunus; , Prof. dr. Hamam Hadi, MS., Sc.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The declining incidence of stunting in Indonesia is very low annually and the incidence of stunting in children under 2 years is correlated with numerous factors, among others are the practice of early breastfeeding initiation, exclusive breastfeeding, infection disease and social economic condition of the family. The practice of early breasfeeding initiation in infants will minimize the incidence of infection disease and encourage exclusive breastfeeding supplementation. Objective: To analyze the protective factor of breastfeeding initiation to the incidence of stunting in children of 6 â 24 months at Yogyakarta Municipality. Method: The study was observational with case control study design. Subject of the study were children of 6 â 24 months at Yogyakarta Municipality. Cases were stunting and controls were non stunting children. Each group consisted of 121 children (1:1). Stunting was defined as length or height/age < -2 SD. Samples were taken through non-probability sampling with consecutive sampling method. Data analysis used univariate with frequency distribution, bivariate with chi square, and multivariate with logistic regression. Result: The result of bivariable of the study showed that children with history of breastfeeding initiation risked 2,3 times lower for the incidence of stunting (OR=0,423